2017
DOI: 10.2174/1874210601711010436
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontic Rehabilitation of Arabic Speaking Individuals with Velopharyngeal Incompetence: A Preliminary Study

Abstract: Background:Hypernasality is a frequently encountered problem in the speech of individuals with velopharyngeal incompetence. The use of palatal lift appliance (PLA) is the main treatment option for correction of velopharyngeal incompetence. The literature on the outcomes of using prosthetics treatment for Arabic speaking patients is scarce.Objective:The aim of this study was to investigate the effect of using PLA on hypernasality of Arabic speaking patients with velopharyngeal incompetence.Methods:Six participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The SNAP Test-R has been adapted for many other languages such as Egyptian Arabic (Abou-Elsaad et al, 2012) and Greek (Okalidou et al, 2011), whereas part of the SNAP Test-R (Syllable Repetition Subtest) has been adapted for Brazilian Portuguese with established normative nasalance scores reported for a wide range of ages, including children, adolescents, young adults, and adults (de Castro Marino et al, 2016). Additionally, several studies have shown that there are differences in nasalance based on age and gender (eg, Brunnegard and Van Doorn, 2009; Abou-Elsaad et al, 2012; Gnanavel et al, 2013; Bibars et al, 2017, Khwaileh and Alfwaress, 2018). In contrast, nasalance scores from the Turkish study on 3 age groups (ages 4-7, 8-12, and 13-18 years) revealed a slight increase in nasalance with age, but no difference in nasalance based on gender (Ünal-Logacev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The SNAP Test-R has been adapted for many other languages such as Egyptian Arabic (Abou-Elsaad et al, 2012) and Greek (Okalidou et al, 2011), whereas part of the SNAP Test-R (Syllable Repetition Subtest) has been adapted for Brazilian Portuguese with established normative nasalance scores reported for a wide range of ages, including children, adolescents, young adults, and adults (de Castro Marino et al, 2016). Additionally, several studies have shown that there are differences in nasalance based on age and gender (eg, Brunnegard and Van Doorn, 2009; Abou-Elsaad et al, 2012; Gnanavel et al, 2013; Bibars et al, 2017, Khwaileh and Alfwaress, 2018). In contrast, nasalance scores from the Turkish study on 3 age groups (ages 4-7, 8-12, and 13-18 years) revealed a slight increase in nasalance with age, but no difference in nasalance based on gender (Ünal-Logacev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%